2007
DOI: 10.5038/2375-0901.10.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Transit Bus Accidents and Promising Collision Countermeasures

Abstract: This article presents information on bus collisions from the National Transit Database (NTD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The expected number of vehicle and clearance collisions was estimated to increase with the number of intersections contained in line haul segments. This result is consistent with Yang's (2007) analysis of NTD data, which found that about 80% of major bus collisions occurred at or near intersections. Estimated collision frequencies are yet greater for signalized intersections, likely reflecting the correspondingly greater volumes of cross traffic and turning movements that occur in that setting.…”
Section: Resultssupporting
confidence: 90%
“…The expected number of vehicle and clearance collisions was estimated to increase with the number of intersections contained in line haul segments. This result is consistent with Yang's (2007) analysis of NTD data, which found that about 80% of major bus collisions occurred at or near intersections. Estimated collision frequencies are yet greater for signalized intersections, likely reflecting the correspondingly greater volumes of cross traffic and turning movements that occur in that setting.…”
Section: Resultssupporting
confidence: 90%
“…The issue of transportation safety issues is also the reason for the condition of road transportation. There are still many aspects that need to be addressed [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The National Transit Database (NTD) was used to study the relationship between transit bus collisions and factors such as road design, weather, lighting, etc. (Yang 2007), but driver distraction was not included as a factor in this study. Due to lack of distraction-reporting by transit drivers, the associated risks and impact on performance is difficult to study and is not well-understood.…”
Section: Introductionmentioning
confidence: 99%